2006
DOI: 10.1007/s00425-005-0215-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biochemical evidence for involvement of HOTHEAD in the biosynthesis of long-chain α-,ω-dicarboxylic fatty acids and formation of extracellular matrix

Abstract: In plants, extracellular matrix polymers built from polysaccharides and cuticular lipids have structural and protective functions. The cuticle is found to be ten times thinner in Arabidopsis thaliana (L.) Heynh than in many other plants, and there is evidence that it is unusual in having a high content of alpha-,omega-dicarboxylic fatty acids (FAs) in its polyesters. We designated the new organ fusion mutant hth-12 after it appeared to be allelic to adhesion of calyx edges (ace) and hothead (hth), upon molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(167 citation statements)
references
References 46 publications
3
164
0
Order By: Relevance
“…S4). OsNP1 belongs to group A, represented by the Arabidopsis protein At1g72970, which was proposed to act as a long-chain fatty acid (LCFA) ω-alcohol dehydrogenase catalyzing the biosynthesis of long-chain α-,ω-dicarboxylic FAs (15). α-,ω-dicarboxylic FAs were proposed to participate in the cross-linking of surface cutin (15).…”
Section: -L)mentioning
confidence: 99%
“…S4). OsNP1 belongs to group A, represented by the Arabidopsis protein At1g72970, which was proposed to act as a long-chain fatty acid (LCFA) ω-alcohol dehydrogenase catalyzing the biosynthesis of long-chain α-,ω-dicarboxylic FAs (15). α-,ω-dicarboxylic FAs were proposed to participate in the cross-linking of surface cutin (15).…”
Section: -L)mentioning
confidence: 99%
“…Chemical analysis indicated that the Arabidopsis hth mutant has wild-type wax levels but abnormal cutin quantity and composition. Specifically, it has decreased levels of dicarboxylic acids and increased amounts of v-hydroxy acids, leading the authors to suggest that HTH may have a role in the oxidation of v-hydroxy fatty acids to the dicarboxylic acid cutin monomers that are characteristic of Arabidopsis stem and leaf cuticles (Kurdyukov et al, 2006b). As dicarboxylic acid cutin monomers are unusually abundant in Arabidopsis, it will be interesting to see whether HTH-related proteins are as essential to cuticle formation in other species where this class of monomers is scarce.…”
Section: Enigmatic Factors In Cuticle Biosynthesismentioning
confidence: 99%
“…In the last few years, the list of genes of cutin biosynthesis in A. thaliana has grown significantly (12,(18)(19)(20)(21)(22)(23)(24)(25). These genes have been shown to affect monomers of stems, leaves, or seeds, but none has been demonstrated to affect the synthesis of the cutin layer in floral organs on the basis of a chemical analysis of cutin.…”
Section: Identification Of Arabidopsis Mutants Lacking Flower Nanoridmentioning
confidence: 99%